The effect of three different pre-match warm-up structures on male professional soccer players’ physical fitness - Ben Brahim, Mehdi; Sal-de-Rellán, Alejandro; García-Valverde, Adrián; Yasin, Hussain; Raya-González, Javier (PeerJ, 2023)
Background Optimizing the soccer players’ match preparation is one of the most relevant concerns of coaches for strength and conditioning training. Thus, the aim of this study was to analyze the effects of three pre-match warm-up structures on the physical condition of male professional soccer players. Materials & Methods Seventeen male professional soccer players (age: 20.9 ± 2.4 years) of one Tunisian Professional Soccer League team participated in this study. Players performed three times a typical pre-match warm-up (WU) [aerobic phase (AE); neuromuscular phase (NM); velocity phase (VL); and ball-specific phase (BS) variating the order of the included phases/exercises: WU1 (AE + BS + NM + VL); WU2 (AE + NM + VL + BS); and WU3 (AE + VL + BS + NM). After each warm-up phase, players completed the following physical fitness tests: linear sprint test, countermovement jump test, 15-m ball dribbling agility test and ball shooting test. Additionally, the rate of perceived exertion (RPE) was registered after each warm-up. Results The results indicated significant differences between WU1 and WU3, with better results in the ball shooting test and RPE in WU3. In addition, there were no significant differences in the other variables and between other warm-up structures. These findings could be of great interest for coaches to the strength and conditioning coaches for professional soccer teams in order to improve the players physical performance and perceived exertion.
Keywords: Physical performance; Football; RPE; Pre-match preparation; Team sport